Ministry Amidst the Refugee Crisis in Europe: Understanding Missionary-Refugee Relationships - Sanchez, Jamie N. (Transformation, 2021)
The purpose of this paper is to present the findings of an investigation into missionary-refugee relationships in Europe. The main research question guiding this study was: How do missionaries understand and describe their relationship with the refugees they serve? The data for this study were collected at an international consultation on ministry with refugees held in the fall of 2017 from 21 missionaries using semi-structured interview protocols. Findings demonstrate that missionaries shared a liminal identity with the refugees in their ministry, viewed hospitality as a Christian lifestyle, perceived Christianity to be an inclusive faith, and discussed the challenges and opportunities in their ministry with refugees. Based on the findings we offer implications for mission theorizing and practice in the 21st century church.